The Effectiveness of Soap-Based Dish Soap Production Training in the Development of Community Entrepreneurship Potential in Binjai Village, Serdang Bedagai, Tebing Tinggi - Nathasyah Putri Maharanni; Fikri Mahessa; Siti Aisyah (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2026)
The demand for dish soap is high, with significant associated costs. PKK women in Binjai Village face limitations in technical skills and entrepreneurial potential, underscoring the need for independent training in liquid soap production to promote cost efficiency and local business development. This community service program aimed to provide training in dish soap production to enhance PKK women's technical skills, motivation, and capacity to initiate microenterprises in Binjai Village. The training was conducted face-to-face, using lectures, discussions, and hands-on practice with materials such as liquid soap, water, basins, and dishes. The soap-based production training demonstrated high effectiveness, evident in participants’ significant improvement in technical skills. The participatory, hands-on method allowed participants to learn by doing and receive immediate feedback for corrections. Using soap as a practical, inexpensive, and safe medium facilitated household-scale production. The program also fostered entrepreneurial potential, marked by tangible initiatives such as the formation of informal production groups and the creation of the local brand “Sabun Binjai.” Understanding production costs and simple branding strengthened financial confidence and a sense of product ownership. Overall, the training enhanced technical skills, entrepreneurial capacity, and social capital within the community. Conclusion: Soap-based training effectively improves technical skills, cultivates entrepreneurial potential, and strengthens the social capital of PKK women, supporting household cost savings and creating opportunities for local business ventures.